Diagonal compression of hollow concrete block masonry, as an indicator of structural vulnerability. - Hernández, Eddisson; Aguilar Arriola, Erasmo José; Martínez, H. (Revista ALCONPAT, 2025)
The objective of this work was to evaluate the performance of artisanal and semi-industrial blocks, used to make prisms and walls, under vertical and diagonal stresses necessary to determine the structural vulnerability of buildings to seismic hazards. Concrete block masonry constructions are commonly used in the Pacific region of Nicaragua, mainly in housing projects. In 2017, the Ministry of Transportation and Infrastructure, published the "Minimum Standard for Design and Construction of Masonry MP-001", as a complement to the National Construction Regulations. However, this standard does not take into account the characteristics and properties of local materials. Concrete blocks prisms and walls were elaborated, and failure types and mechanical performance at later ages were determined. The results showed a tendency to diagonal stress failures in walls, with an average strength (Vm) of 6.7 kg/cm2, higher than those reported in the literature.